Reviving indigenous water management practices in Morocco - Simon, Sandrine, 1970- author.
1 online resource.
Keywords: "This book demonstrates how Morocco and other semi-arid countries can find solutions to water scarcity by rediscovering traditional methods of water resource management. The book begins by examining indigenous water heritage, considering the contribution of Islam and the mixed heritage influences of Middle Eastern, Andalusian and Berber cultures. It provides a thorough examination of historical resource management practices in Morocco, tracing the changing patterns from the instillation of agrarian capitalism in the 19th Century, through the Protectorate years (1912-1956), to the 21st Century. The book then explains how reviving and modernizing traditional methods of water management provides simple, accessible and successful methods for addressing 21st Century challenges, such as water scarcity and climate change. The work concludes by highlighting how these indigenous practices can be used to provide real-world practical solutions for improving water governance and therefore developing sustainable water management practices. Reviving Indigenous Water Management Practices in Morocco will be of great interest to students and scholars of water resource management, indigenous peoples and traditional knowledge and sustainable development"--